THE INFLUENCE OF THE DYRRACHIUM POTTERY WORKSHOPS IN CENTRAL AND SOUTH DALMATIA - Šešelj, Lucijana (Rei Cretariae Romanae Fautorum Acta, 2024)
In recent years the archaeological excavations of the Hellenistic sites in Dalmatia have revealed a huge amount of Hellenistic pottery. Excavations of the sanctuaries of Diomedes at Palagruža and Cape Ploča, and the sanctuary in Cave Nakovana yielded various types of Hellenistic pottery and an opportunity to study it in a more thorough way. But the problems of origin, production and chronology still remain.